Effectiveness of Self-Management in Improving Glycemic Control Among Patients with Type 2 Diabetes Mellitus: A Literature Review - Elin Angraini; Hernizah; Erika (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2026)
Type 2 diabetes mellitus is a chronic disease that requires continuous management to prevent complications. One important approach is self-management, which includes patients’ ability to regulate diet, physical activity, treatment adherence, and independent monitoring of blood glucose levels. This study aimed to analyze the effectiveness of self-management interventions on glycemic control in patients with type 2 diabetes mellitus. The method used was a literature review, with databases including PubMed, ScienceDirect, and Google Scholar. The keywords used were “self-management,” “type 2 diabetes mellitus,” “glycemic control,” “HbA1c,” and “DSMES.” A total of 10 articles were obtained from the literature search. The selected articles were screened using predefined inclusion and exclusion criteria, and methodological quality was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Tools. The results of the review indicate that diabetes self-management education and support (DSMES) interventions generally have a positive effect on reducing HbA1c levels and improving patients’ self-care behaviors. However, the effectiveness of the intervention varies depending on program duration, delivery methods, and population characteristics. In addition, social support factors and the use of digital technology contribute to enhancing the success of self-management. In conclusion, self-management interventions may contribute to improving glycemic control in patients with type 2 diabetes mellitus, but it requires a continuous, integrated, and patient-centered approach.